A polymer-ceramic composite membrane for the oil/water separation with enhanced antifouling performance. (9th September 2020) - Jin, Xiaopan; Peng, Shuge; Chen, Yamin; Ma, Junying; Niu, Qingshan
Abstract: To improve the antifouling property of ceramic membrane in oil/water separation, a high flux and antifouling polymer–ceramic composite membrane (PI/CM) was prepared by a modified method. FESEM, EDS and CA were used to characterize the morphology, surface composition, and surface characteristics of the as-prepared PI/CM composites; and the pore size distribution was measured with bubble point porometer technique. The oil/water mixture separation and antifouling effects of the PI/CM modification membrane were evaluated by the filtration tests using edible oil as model foulant. The results showed that the polyimide (PI) with low molecular weight was grafted on the surface of CM via our modified method. The most probable pore size of the PI/CM composite membrane decreased to 542.9 nm, which was less than 849.9 nm of the raw CM. During this microfiltration of oil/water mixture at the constant applied pressure of 0.86 bar, the modified PI/CM showed a high water flux of 2430 LMH, which was comparable to the raw CM. While the edible oil rejection rate was up to 96.5% for the oil/water mixture, far higher than CM; and the PI/CM also showed a good anti-fouling property with a far higher water flux recovery of 88.8% than CM. Moreover, the special structural stability of the modified membrane profited from the strong interaction between polyimide and CM endowed it with better durability in oil/water mixture than CM during repeated filtration.